2021
DOI: 10.3390/geosciences11060249
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Earthquake Damage Estimation to the Input Data (Soil Characterization Maps and Building Exposure): Case Study in the Luchon Valley, France

Abstract: This article studies the effects of the soil data and exposure data of residential building inventories, as well as their spatial resolution, on seismic damage and loss estimates for a given earthquake scenario. Our aim is to investigate how beneficial it would be to acquire higher resolution inventories at the cost of additional effort and resources. Seismic damage computations are used to evaluate the relative influence of varying spatial resolution on a given damage model, where other parameters were held c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…For example, the gridded exposure can be improved by weighting site properties within each grid cell or considering variable grids denser around the main faults and where site properties tend to vary. In addition, while this work has focused on regional scale risk studies, further analysis should be undertaken at sub-regional and urban scale in order to understand where a suitable balance can be struck between exposure resolution, uncertainty characterization and computational cost, when more detailed information may be available (e.g., Fayjaloun et al 2021). Since the effects of data resolution depend strongly on the variation in the hazard (see the discussion), future studies should focus on mitigating the bias at the ground motion level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the gridded exposure can be improved by weighting site properties within each grid cell or considering variable grids denser around the main faults and where site properties tend to vary. In addition, while this work has focused on regional scale risk studies, further analysis should be undertaken at sub-regional and urban scale in order to understand where a suitable balance can be struck between exposure resolution, uncertainty characterization and computational cost, when more detailed information may be available (e.g., Fayjaloun et al 2021). Since the effects of data resolution depend strongly on the variation in the hazard (see the discussion), future studies should focus on mitigating the bias at the ground motion level.…”
Section: Discussionmentioning
confidence: 99%
“…The large difference in horizontal ground vibration PGV Hmod values at the individual station is not explained by the values of vibration amplification coefficient W f at the point of registration. Bearing in mind that seismic waves propagation is affected by lithostratigraphic and topographic local conditions-e.g., [26][27][28][29][30][31][32][33][34], the distribution of the amplification factor W f is shown in Figure 5. The error in determining the value PGV H indicates that the standard deviation S = 0.314.…”
Section: Ground Vibrationsmentioning
confidence: 99%
“…They concluded that amplification factors are best predicted as a function of V s30 in conjunction with the dominant period of the site and the shear wave velocity gradient. Fayjaloun et al [20] investigated the damage scenario of residential buildings shaken by moderate ground acceleration (200 cm 2 /s) with and without consideration for the site amplification factor of 1.5. It is noted from Régnier et al [21,22] that the EQL analysis should be considered reliable with reference to PGA lower than 0.2-0.3 g.…”
Section: Introductionmentioning
confidence: 99%